Impact of organizational justice and manager's mental health on staff nurses' affective commitment: A multilevel analysis of the work environment of hospital nurses in Japan-Part II (WENS-J-II) - Ayano Ito; Miki Sasaki; Yuki Yonekura; Yasuko Ogata (Elsevier, 2023)
Background: Nursing shortage is a global and priority issue. Affective commitment has been identified as a key to retention in the workplace. Exploring the way to promote the nurse's affective commitment is necessary to maintain the nursing workforce and care quality. The staff nurse's organizational justice (procedural and interactional justice) and the manager's condition of mental health have the potential to be related to the staff nurse's affective commitment. Objective: To explore the impact on the nurse's affective commitment from procedural and interactional justices at individual and unit levels and the manager's mental health. Design: A multi-site longitudinal design. Setting(s): Nine Japanese hospitals with more than 200 beds and located in an area with more than 150,000 people. Participants: 385 staff nurses and their 42 nurse managers who completed both surveys in 2016 and 2017. Methods: We analyzed the data from a two-year national survey of the Work Environment for hospital Nurses in Japan part II. Nurse staff and their managers completed the surveys. This multilevel analysis performed four random intercept models on affective commitment and entered the variables of procedural and interactional justices and manager mental health into the models. Results: The staff nurse's affective commitment was positively associated with procedural justice climate (unit level), interactional justice climate (unit-level), and the perception of interactional justice (individual justice). The manager's mental health (psychological distress) had a negative relationship with affective commitment. Conclusions: The climates of procedural and interactional justice, the individual perception of interactional justice, and the manager's mental health impacted the nurses' affective commitment as a predictor of retention. Moreover, the perception of interactional justice and the organizational contexts (organizational justice climates and managers' psychological distress) were mediated by affective commitment. Thus, support to maintain the manager's mental health is required to promote staff's affective commitment related to retention. Registration: None. Tweetable abstract: Nurse staff's affective commitment was stimulated by interactional justice, two types of organizational justice climate, and the manager's mental health.